Self-Defense Justifications: from Caroline Case to Russia v Ukraine - Putra, Jaya Indra Santosa; Sefriani, Sefriani; Febriani, Yasyfa; Khoirunnisa, Hafara; Ramadhan, Muhammad Rizki (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
Russia's invasion of Ukraine on February 24, 2022, attracted international attention when Russia justified the invasion as an act of self-defense based on Article 51 of the UN Charter. This study is a normative legal study that aims to analyze the role of International Customary Laws in determining the legality of the use of self-defense, particularly on Russia’s claims in the armed conflict with Ukraine. This study employed conceptual, statutory, political, and historical approaches. In adherence to Article 51 of the UN Charter, relevant Customary International Laws such as the Caroline Test and supplemental relevant rulings from the International Court of Justice were considered essential in evaluating and determining the legality of self-defense. Based on the legal standards set forth in the Caroline Test and ICJ’s Rulings, Russia's use of self-defense failed to fulfil the imminency, proportionality, and necessity standards, making the actions illegitimate under International Law. Hence, the action was invalid according to international law.